Produção e qualidade de morangos em cultivo protegido consorciado com a figueira - Mendonça, Heloísa Ferro Constâncio (2011)
The consumer demands quality, convenience, safe and healthy food producers want high yield and stable performance of the crops. In this way, more research is needed looking technologies to meet both producers and final consumers. The use of greenhouse horticulture has been used as it provides increased earliness and yield, besides the offseason production, among other advantages. Therefore, this research studied the feasibility of intercropping produced the fig tree in a protected environment with the strawberry on the substrate and in this single system. To achieve this goal, the work was divided into two experiments. At first it was determined phylochron of strawberry cultivars in both cropping systems and agronomic feasibility of the second consort fig produced in protected strawberry in the substrate and in this single system. The survey was conducted in two greenhouses at the University of Passo Fundo, in the period of 03 May 3 2009 to May 30, 2010, including the period of transplantation at the end of the strawberry crop of fig. Cultivars were evaluated, Florida Festival, Camino Real and Earlibrite (seedlings from Argentina), and Flavors, Camino Real, Albion, Camarosa and Ventana (seedlings coming from Chile) produced in polyethylene bags filled with white commercial substrate Tecnomax ®. Treatments (cultivars) were arranged in a randomized block design with four replications. We assessed the phenology, yield and fruit quality of strawberry cultivars in both systems. In fig cv. Purple Valinhos was examined phenology, fruit number per branch and per plant and yield. The results were subjected to analysis of variance and differences compared by Tukey test at 5% significance level. Through the accumulation of leaves and the income is verified that the strawberry cultivars can be intercropped with fig cv. Roxo de Valinhos. The productivity of the intercropping system was superior to single, except for Ventana. Earlibrite Florida Festival and reach peak production in October in both systems. When intercropped cultivars multiplied in Chile and also Camino Real Nursery Argentine offer maximum production in November, but Ventana is grown without being cropped, has its peak in September and October